2020
DOI: 10.22603/ssrr.2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Evaluation of Lumbar Arteries for Lateral Lumbar Interbody Fusion with Magnetic Resonance Imaging

Abstract: Introduction: Lateral lumbar interbody fusion (LLIF) is becoming a more common surgical treatment option for adult degenerative lumbar conditions. LLIF is a mini-open access technique with wound retractors, and postoperative hematoma due to segmental vessels injury is reported. Thus, it is considered that there is a need to conduct detailed preoperative examinations to identify where the lumbar vessels are. As far as we know, there are only a few studies investigating the location of the lumbar arteries. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Also, it is quite clear in recent studies, that the presence of vascular injuries and postoperative venous thrombosis leads to increased transfusion rates, morbidity, and in-hospital mortality, as highlighted by Goot et al, where the most cases of injury signed in the left common iliac vein (LCIV) [ 19 - 20 ]. On the other hand, Chiriano et al reported that by anterior retroperitoneal access to the lumbar spine (ARES), the frequency of vascular injury in cases involving the disc of L4-L5 was higher in comparison with the other levels while CIV laceration was associated with higher rates of postoperative deep vein thrombosis [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…Also, it is quite clear in recent studies, that the presence of vascular injuries and postoperative venous thrombosis leads to increased transfusion rates, morbidity, and in-hospital mortality, as highlighted by Goot et al, where the most cases of injury signed in the left common iliac vein (LCIV) [ 19 - 20 ]. On the other hand, Chiriano et al reported that by anterior retroperitoneal access to the lumbar spine (ARES), the frequency of vascular injury in cases involving the disc of L4-L5 was higher in comparison with the other levels while CIV laceration was associated with higher rates of postoperative deep vein thrombosis [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…There are some reports on the anatomical evaluation of arteries in the cervical and lumbar spine. [11][12][13][14] Meanwhile, a few cadaver studies on the thoracic spine have been reported, with no previous detailed analysis using 3D-CT in the upper to middle thoracic spine. This study aimed to investigate the anatomical characteristics and variations of the thoracic segmental arteries.…”
mentioning
confidence: 99%
“…Computed tomography angiography (CTA) and 3D reconstruction images have helped develop human vascular anatomy, provided a view similar to surgical anatomy, and aided in diagnosis and preoperative planning. There are some reports on the anatomical evaluation of arteries in the cervical and lumbar spine 11–14. Meanwhile, a few cadaver studies on the thoracic spine have been reported, with no previous detailed analysis using 3D-CT in the upper to middle thoracic spine.…”
mentioning
confidence: 99%
“…16 Recently, MRI of patients with lumbar disease has shown that lumbar vessels are not necessarily located at the center of the vertebral body since many individual differences occur, especially in L4, where the lumbar vessels verge down from the anterior cranial side to the posterior caudal side. 17 However, results coming from MRI can suffer from a low accurate…”
mentioning
confidence: 99%